2023
DOI: 10.1186/s13058-023-01615-6
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in RAD51 expression are regulated by miRNA-214-5P and its inhibition synergizes with olaparib in triple-negative breast cancer

Abstract: Background Triple-negative breast cancer (TNBC) affects young women and is the most aggressive subtype of breast cancer (BC). TNBCs disproportionally affect women of African-American (AA) descent compared to other ethnicities. We have identified DNA repair gene RAD51 as a poor prognosis marker in TNBC and its posttranscriptional regulation through microRNAs (miRNAs). This study aims to delineate the mechanisms leading to RAD51 upregulation and develop novel therapeutic combinations to effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…[ 27 , 28 ] The development of robust biomarkers for treatment response prediction is essential, encompassing genetic, epigenetic, and proteomic markers to refine patient selection and tailor treatment strategies. [ 29 ] Additionally, cohort studies across diverse populations are crucial for addressing treatment disparities and improving outcomes. [ 30 , 31 ] Ultimately, advancing OC treatment requires a multi-faceted approach, integrating innovative therapies, precision oncology, and comprehensive patient studies to personalize and improve care for this complex condition.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 , 28 ] The development of robust biomarkers for treatment response prediction is essential, encompassing genetic, epigenetic, and proteomic markers to refine patient selection and tailor treatment strategies. [ 29 ] Additionally, cohort studies across diverse populations are crucial for addressing treatment disparities and improving outcomes. [ 30 , 31 ] Ultimately, advancing OC treatment requires a multi-faceted approach, integrating innovative therapies, precision oncology, and comprehensive patient studies to personalize and improve care for this complex condition.…”
Section: Discussionmentioning
confidence: 99%
“…And these outcomes hints at potential mechanisms by which thyroid dysfunction might influence breast cancer, indicating potential mechanisms of TT3, TT4, FT3, FT4, TSH, TPOAb, and TgAb regulating the tumor microenvironment in breast cancer. [ 5 , 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…The primary cause of recurrence is the spread of breast cancer cells, with triple-negative breast cancer cells being an aggressive and difficult-to-treat type of breast cancer associated with a poor prognosis. [ 6 8 ] Different changes in key genes and pathways are involved in the metastasis process of various types of breast cancer cell lines. Furthermore, deaths reported in previous studies can be attributed to drug resistance and breast cancer subtypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were results suggested that a novel combination of miR-214-5P and olaparib could be an effective therapy for BRCA-wild-type TNBCs and reduce racial disparities in TNBC outcomes. [ 44 ] SPON2 intervention can be further studied. Ming Wu et al(2023) found that SPON2 promotes the bone metastasis of lung adenocarcinoma via activation of the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%